ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS DAN PROFITABILITAS PADA PT. ASTRA INTERNASIONAL TBK - APRIYANTI, NURLITA; MUNANDAR, ARIS; MUTHIAH, HANIFAH (GANEC SWARA, 2024)
This reseach was conducted at PT. Astra Internasional Tbk. The aim of this reseach is to analyze and explain finansial performance as measured by the Current Ratio (CR) and Net Profit Margin (NPM) at PT. Astra Internasional Tbk, through financial report analysis of the company’s ability to fulfill its obligations and the results achieved from its operational activities, the type of research carried out is descriptive reseach. The results of descriptive and statistical analysis showed that PT. Astra Internasional Tbk’s Current ratio is in poor condition, this indicates that the company has not been able to pay short-term obligations or debts that are due. The Net Profit Margin is in poor condition, this indicates that the company has not been able to maximize net profit from the company’s operational activities.